Paciente masculino de 55 años de edad presenta enfermedad Cardiaca Hipertensiva - Riascos Florencia, Joely Felicita (2018)
The hypertensive heart disease in synthesis is a consequence of arterial hypertension, since it is a disorder that includes the alterations of the heart and the systemic circulation of the same one. Arterial hypertension can be defined as a complication of Cardiac Expenditure since it is developed by a peripheral resistance that occurs from the blood vessels to the flow of blood. The present case study deals with a 55-year-old male patient who presented to the hospital area due to hypertensive crisis with symptoms of chest pain, orthopnea with malaise, decay, asthenia and altered levels of pain. Glucose in the blood. The patient was assessed globally to be able to make a timely dietary prescription and thus managed to correct the nutritional habits present in this pathology. An anthropometric assessment was performed which resulted in Obesity grade III (morbid), after this a nutritional plan was prepared according to their caloric needs where the diet is 1900 kcal / day, hypoglycemic and divided into 4 meals and with the intervention of physical exercise that was 45 minutes a day by means of dance, aerobics and walks, it was possible to take control of the body weight and reach the Adjusted weight, which is 87kg. During 6 months the glycemia control was carried out every 2 months where it could be noticed that the glucose values in the blood decreased as the patient adapted to the changes in their diet.